2010
DOI: 10.1021/ef901538m
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Electrochemical Capacitors Based on NaOH- and KOH-Activated Carbons

Abstract: This work describes the chemical activation of a coke using two different activating agents in order to investigate their behaviour as electrodes in supercapacitors. A coke was chemically activated with two hydroxides (KOH and NaOH) under nitrogen flow, at a constant mass hydroxide/coke ratio of 2 and temperatures of 600, 650 and 700 ºC. All the samples were characterized in terms of porosity by N 2 sorption at 77 K, surface chemistry by temperature programmed desorption (TPD) and electrical conductivity. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…96 Bleda-Martínez et al found also a good correlation between the specic capacitance of activated carbons and the amount of surface oxygen groups desorbing as CO. 48 Many other reports on pseudocapacitance contribution of oxygengroups in activated carbons are available. [188][189][190][191][192][193][194] Oxidation treatments, both chemical (HNO 3 or H 2 SO 4 ) and electrochemical, have also been applied to activated carbons to generate oxygen-containing functionalities, increasing the specic capacitance of the material. [195][196][197][198][199] Additionally, Mysyk et al have shown that a high concentration of oxygenated surface functionalities can prevent further oxidation of the activated carbon, allowing operation in a wider potential window.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…96 Bleda-Martínez et al found also a good correlation between the specic capacitance of activated carbons and the amount of surface oxygen groups desorbing as CO. 48 Many other reports on pseudocapacitance contribution of oxygengroups in activated carbons are available. [188][189][190][191][192][193][194] Oxidation treatments, both chemical (HNO 3 or H 2 SO 4 ) and electrochemical, have also been applied to activated carbons to generate oxygen-containing functionalities, increasing the specic capacitance of the material. [195][196][197][198][199] Additionally, Mysyk et al have shown that a high concentration of oxygenated surface functionalities can prevent further oxidation of the activated carbon, allowing operation in a wider potential window.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…It is well known that the morphology of the OMC (including specific surface area, pore size and volume) can be altered by post‐synthesis modification. In industries, KOH activation is a common method usually employed to generate micropores in activated carbon ,. The activation conditions such as temperature, concentration and other to facilitate the merging of micropores to get mesopores.…”
Section: Resultsmentioning
confidence: 85%
“…According to the literature, the pseudocapacitive effect is described by the following reaction (Eq. 1) [32].…”
Section: Resultsmentioning
confidence: 99%